2021
DOI: 10.1107/s2052252521000774
|View full text |Cite
|
Sign up to set email alerts
|

Coherent crystal branches: the impact of tetragonal symmetry on the 2D confined polymer nanostructure

Abstract: The symmetry of polymer crystals greatly affects the optical, thermal conductivity and mechanical properties of the materials. Past studies have shown that the two-dimensional (2D) confined crystallization of polymer nanorods could produce anisotropic structures. However, few researchers have focused on understanding confined nanostructures from the perspective of crystal symmetry. In this research, we demonstrate the molecular chain self-assembly of tetragonal crystals under cylindrical confinement. We specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These diffractions were assigned to (001), (200), (220), (3 true1¯ 1), (2 true1¯ 2), (3 true2¯ 1), (4 true1¯ 1), and (420) crystal planes of Form I considering their two‐theta value. For the sample without any treatment, the intensity distribution of the diffraction indicates an anisotropic structure in the sample 40 . As T h was higher than 236°C, the intensity distribution of the diffraction was changed obviously from a combination of arc and circle to full circle with increasing T h , indicating a transition of orientation from oriented to randomly distributed one.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These diffractions were assigned to (001), (200), (220), (3 true1¯ 1), (2 true1¯ 2), (3 true2¯ 1), (4 true1¯ 1), and (420) crystal planes of Form I considering their two‐theta value. For the sample without any treatment, the intensity distribution of the diffraction indicates an anisotropic structure in the sample 40 . As T h was higher than 236°C, the intensity distribution of the diffraction was changed obviously from a combination of arc and circle to full circle with increasing T h , indicating a transition of orientation from oriented to randomly distributed one.…”
Section: Resultsmentioning
confidence: 94%
“…For the sample without any treatment, the intensity distribution of the diffraction indicates an anisotropic structure in the sample. 40 As T h was higher than 236 C, the intensity distribution of the diffraction was changed obviously from a combination of arc and circle to full circle with increasing T h , indicating a transition of orientation from oriented to randomly distributed one.…”
Section: Uniaxial Stretching and In-situ Synchrotron Xray Scattering ...mentioning
confidence: 91%
“…It was shown that this source can be used to provide gallium (9.3 keV) or indium (24.2 keV) K radiation (Otendal et al, 2008;Larsson et al, 2011). However, only the softer gallium radiation has been used for structure determination by singlecrystal X-ray diffraction experiments so far (Chan et al, 2018;Klein et al, 2017;Liang et al, 2021;Mehr et al, 2020;Pan et al, 2017). Initial experiments showing that diffraction data can also be obtained with indium radiation have been reported recently in a PhD thesis (No ¨thling, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[51] Since its introduction, the MetalJet X-ray source has been used in single crystal X-ray diffraction studies involving all kinds of different compounds. From small organic molecules [59][60][61][62][63][64] to proteins, [65][66][67][68] polymers [69,70] and metal organic frameworks. [71] Furthermore inorganic compounds containing p-block elements [72,73] as well as d-metal complexes [74][75][76][77][78][79][80] have been investigated.…”
Section: Metaljet X-ray Sourcementioning
confidence: 99%